Carotid Artery Stiffness is Associated With Cognitive Performance in Former Smokers With and Without Chronic Obstructive Pulmonary Disease. Issue 9 (5th May 2020) - Hoth, Karin F.; Moreau, Kerrie L.; Weinberger, Howard D.; Holm, Kristen E.; Meschede, Kimberly; Crapo, James D.; Make, Barry J.; Moser, David J.; Kozora, Elizabeth; Bowler, Russell P.; Pierce, Gary L.; Ten Eyck, Patrick; et al.
Abstract : Background: Heavy smokers perform worse on neuropsychological assessment than age‐matched peers. However, traditional pulmonary measures of airflow limitation and hypoxemia explain only a modest amount of variance in cognition. The current objective was to determine whether carotid artery stiffness is associated with cognition in former smokers beyond the effects of amount of smoking and pulmonary function. Methods and Results: Eighty‐four former smokers including individuals across a spectrum of airflow limitation severity were included: 30 without chronic obstructive pulmonary disease (Global Initiative for Chronic Obstructive Lung Disease [GOLD] 0 with normal spirometry and lung computed tomography), 31 with mild‐moderate chronic obstructive pulmonary disease (GOLD 1–2), and 23 with severe‐very severe chronic obstructive pulmonary disease (GOLD 3–4). Participants completed questionnaires, spirometry, carotid ultrasonography, and neuropsychological testing. Multiple linear regression was used to determine whether carotid artery stiffness is associated with neuropsychological performance in 4 cognitive domains after adjusting for age, sex, pack‐years of smoking, estimated premorbid intellectual functioning, and airflow limitation. Higher carotid artery β‐stiffness index was associated with reduced executive functioning‐processing speed in the fully adjusted model (β=−0.49, SE=0.14; P =0.001). Lower premorbid intellectual function, male sex, and presence of airflow limitation (GOLD 1 or 2 and GOLD 3 or 4) were also associated with worse executive functioning‐processing speed. β‐Stiffness index was not significantly associated with performance in other cognitive domains. Conclusions: Carotid artery stiffness is associated with worse performance on executive functioning‐processing speed in former smokers beyond the effects of aging, amount of past smoking, severity of airflow limitation, and hypoxemia. Future research should examine whether carotid stiffness can be used to identify former smokers at risk for subsequent cognitive impairment.